A case study of controlling the weight loss of an elite weightlifter on changes in athletic performance - Qu, C.; Fan, Y. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. I, 2008)
Introduction: The purpose of this study was to investigate the change in athletic performance of a weightlifter undergoing body weight reduction, with the view to maintain sports performance after weight loss. Methods A 105.0kg level weight-lifter, Zhang of Yunnan province, was the sole subject of this study and the subject`s baseline body weight was 111.6kg. The test period was from August 15 to November 4, 2007. The athlete was supplied with nutrient-enriched foods including weight-loss bars, L-carnitine capsules, vitamins and electrolytes both during and after weight reduction. The athlete performed physical function tests every fortnight during the test period, and the test indicators included body composition, HRC, HCT, Hb, CK, BUN and T. The sporting ability of the athlete was also tested before and after weight-loss. Results During the period of the study the athlete`s weight decreased from 111.6kg to 93.8kg, lean mass decreased from 69.5kg to 65.0kg and body fat mass decreased from 41.6kg to 28.4kg. The blood indicators which were tested showed some changes during weight reduction and after the weight-loss. The HRC, HCT and Hb plasma levels remained stable, however T levels decreased continuously from 945ng/dl to 450ng/dl. CK and BUN levels were maintained in the normal range. Compared to baseline data the athlete`s sporting ability decreased after weight loss., The athlete`s snatch results decreased by 12 kg while the clean and jerk results decreased by 18 kg. Conclusions A large-scale reduction in body weight needs to be divided into stages and be implemented in steps. During weight reduction the athlete`s body functions and movement abilities need to be maintained.. Large scale weight reduction may have a tremendous influence on sports ability in the short term and optimal methods of rapid reduction in terms of performance vary from person to person.